Actin Cytoskeleton-Dependent Dynamics of the Human Serotonin(1A) Receptor Correlates with Receptor Signaling - Ganguly, Sourav (The Biophysical Society, 2008)
Analyzing the dynamics of membrane proteins in the context of cellular signaling represents a challenging problem in contemporary cell biology. Lateral diffusion of lipids and proteins in the cell membrane is known to be influenced by the cytoskeleton. In this work, we explored the role of the actin cytoskeleton on the mobility of the serotonin(1A) (5-HT(1A)) receptor, stably expressed in CHO cells, and its implications in signaling. FRAP analysis of 5-HT(1A)R-EYFP shows that destabilization of the actin cytoskeleton induced by either CD or elevation of cAMP levels mediated by forskolin results in an increase in the mobile fraction of the receptor. The increase in the mobile fraction is accompanied by a corresponding increase in the signaling efficiency of the receptor. Interestingly, with increasing concentrations of CD used, the increase in the mobile fraction exhibited a correlation of ∼0.95 with the efficiency in ligand-mediated signaling of the receptor. Radioligand binding and G-protein coupling of the receptor were found to be unaffected upon treatment with CD. Our results suggest that signaling by the serotonin(1A) receptor is correlated with receptor mobility, implying thereby that the actin cytoskeleton could play a regulatory role in receptor signaling. These results may have potential significance in the context of signaling by GPCRs in general and in the understanding of GPCR-cytoskeleton interactions with respect to receptor signaling in particular.